The Role of Financial Statements in Management Decision-Making at PT. Pasific Tuna Mandiri - Juliedi Manuel Pelenewen (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
Financial statements are a critical source of information that supports management in planning, controlling, and evaluating corporate activities. Accurate and timely financial data enables management to make effective decisions to achieve organizational objectives. This study aims to analyze the role of financial statements in management decision-making at PT. Pasific Tuna Mandiri. The research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving management and the company's finance department. The collected data were analyzed through data reduction, data presentation, and drawing conclusions. The results indicate that financial statements play a vital role in supporting management decision-making. They are utilized to assess the company’s financial health, control operational costs, prepare budgets, evaluate performance, and formulate strategic business policies. Additionally, financial statements assist management in identifying business opportunities and potential risks that may impact corporate sustainability. The availability of relevant, accurate, and timely financial information allows management to make more effective and efficient choices. Consequently, financial statements serve not only as a reporting tool but also as a strategic instrument that drives organizational performance and business development at PT. Pasific Tuna Mandiri.